Образ океана в волшебной сказке и научной фантастике - Кибалка, Е. (Літературознавчі обрії. Праці молодих учених, 2010)
The article investigates the poetics of magic fairy-tale ocean, images of island and ship in science fiction works by R. Bradbury, C. Simak, A. Strugatskij and B. Strugatskij, K. Byluchev. An attempt is made to determine principles of interaction of folklore, literary and science fiction methods in the construction of the images of ocean, island and ship. The main tendency of interpretation of ocean in science fiction texts is studied.